Peganutonin A: computationally informed synthesis of its revised structure - Saranya, N. Sathya Sai; Choudhury, Rahul; Supekar, Prathmesh R.; Beduru, Srinivas; Williams, Craig M.; Elyashberg, Mikhail E.; Kutateladze, Andrei G.; Bates, Roderick W.; Reddy, D. Srinivasa (Journal of Natural Products, 2025)
The structure of the recently isolated natural product peganutonin A was shown to be incorrect by analysis of the reported spectroscopic data, and therefore, the structure was reassigned utilizing computational methods. Subsequently, the computationally proposed reassignment was confirmed by total synthesis, which was achieved in seven steps from 6-methoxyindole. It is assumed that peganutonin A is not a natural product but an artifact arising from photooxidation of the alkaloid harmaline.